2021
DOI: 10.1161/circresaha.120.317244
|View full text |Cite
|
Sign up to set email alerts
|

Mir-30d Regulates Cardiac Remodeling by Intracellular and Paracrine Signaling

Abstract: Rationale: Previous translational studies implicate plasma extracellular microRNA-30d (miR-30d) as a biomarker in left ventricular (LV) remodeling and clinical outcome in heart failure (HF) patients, though precise mechanisms remain obscure. Objective: To investigate the mechanism of miR-30d-mediated cardioprotection in HF. Methods and Results: In rat and mouse models of ischemic HF, we show that miR-30d gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 58 publications
4
88
0
Order By: Relevance
“…The miR-425 has been reported to have anti-fibrotic effect on heart by inhibiting TGFβ1 (44). The expression of miR-30d, which is selectively enriched in cardiomyocytes, is induced by hypoxic stress and inhibits MAP4K4 to reduce cardiac apoptosis (45). The miR-151 targets PLM and is known to prevent ischemia-induced arrhythmias (46).…”
Section: Discussionmentioning
confidence: 99%
“…The miR-425 has been reported to have anti-fibrotic effect on heart by inhibiting TGFβ1 (44). The expression of miR-30d, which is selectively enriched in cardiomyocytes, is induced by hypoxic stress and inhibits MAP4K4 to reduce cardiac apoptosis (45). The miR-151 targets PLM and is known to prevent ischemia-induced arrhythmias (46).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, cardiomyocyte-specific overexpression of calcineurin leads to an increase in collagen gene expression in the myocardium ( 62 ). Most recently, Li et al ( 63 ) demonstrated that miR-30d in cardiomyocytes may regulate fibroblasts’ activation via targeting integrin α 5 , and cardiomyocytes can release miR-30d–containing extracellular vesicles to inhibit fibroblast proliferation and activation, thus suppressing myocardium fibrosis in ischemic heart failure. Hence, miR-30 downregulation in cardiomyocytes may indirectly and directly activate fibroblasts and promote cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HF show lower levels of circulating miR-30d correlated with an adverse clinical outcome ( Melman et al, 2015 ; Xiao et al, 2017 ). In the rat and mouse models of ischemic HF, overexpression of miR-30d protects against cardiomyocyte apoptosis, myocardial fibrosis and improves cardiac remodeling, while miR-30d silencing causes opposite effects ( Li et al, 2021 ). Of interest, in pulmonary fibrosis miR-30d overexpression induces the activation of Notch signaling by regulating Jagged1 ( Zhao et al, 2018 ).…”
Section: Notch In Heart Failurementioning
confidence: 99%